2022
DOI: 10.1038/s41698-022-00310-7
|View full text |Cite
|
Sign up to set email alerts
|

SRC-RAC1 signaling drives drug resistance to BRAF inhibition in de-differentiated cutaneous melanomas

Abstract: Rare gain-of-function mutations in RAC1 drive drug resistance to targeted BRAF inhibition in cutaneous melanoma. Here, we show that wildtype RAC1 is a critical driver of growth and drug resistance, but only in a subset of melanomas with elevated markers of de-differentiation. Similarly, SRC inhibition also selectively sensitized de-differentiated melanomas to BRAF inhibition. One possible mechanism may be the suppression of the de-differentiated state, as SRC and RAC1 maintained markers of de-differentiation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…SFK induction during targeted therapy treatment has been described in multiple cancers, including melanoma; 30,31,32 our study sheds light on the kinetics associated with this response, revealing that signs of SFK induction can emerge as early as 3-6 hours of oncoprotein inhibition. This onset is markedly earlier than previously appreciated, suggesting a more immediate cellular adaptation to targeted therapy via this axis than previously appreciated.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…SFK induction during targeted therapy treatment has been described in multiple cancers, including melanoma; 30,31,32 our study sheds light on the kinetics associated with this response, revealing that signs of SFK induction can emerge as early as 3-6 hours of oncoprotein inhibition. This onset is markedly earlier than previously appreciated, suggesting a more immediate cellular adaptation to targeted therapy via this axis than previously appreciated.…”
Section: Discussionmentioning
confidence: 53%
“…SFKs constitute a group of non-receptor tyrosine kinases that coordinate important signaling events regulating cell morphology, survival, and metabolism, among many other biological processes, and have been linked to adaptation and resistance to targeted therapy. 30,31,32,33 Many of these phosphosites, in addition to other known SFK substrates which were not in SM-J or SM-K, were upregulated under VEM treatment after 72 hours compared to DMSO-treated cells, suggesting their induction was not a consequence of sustained culture. Notably, some of these sites did not show corresponding increases in transcript abundance, indicating that VEM treatment modulates SFK signaling by mechanisms that are at least partly uncoupled from transcriptional upregulation (Figure S4A).…”
Section: Resultsmentioning
confidence: 98%
“…A375 and 451Lu can be distinguished from the other cell lines based on the expression of the de-differentiated transcriptional program. 46
Figure 3 Performance of candidates (A) Schematic of potential mechanisms by which candidates drive drug resistance. (B) Representative western blot with indicated antibodies in a panel of melanoma cell lines engineered to overexpress the screen candidates, empty vector (EM), VAV1, PDGFRB, or CSF1R.
…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that overexpression of VAV1 increases RAC1 signaling and promotes drug resistance to BRAFi in cutaneous melanoma. 11 , 46 , 49 , 50 To determine the overlap between VAV1 and RAC1 signaling, we performed RNA-seq on A375 with enforced expression of VAV1 or RAC1 P29S ( Figure 4 A). The RAC1 P29S mutation is observed in ∼3% of cutaneous melanomas and encodes a hyperactive form of RAC1 that drives BRAFi resistance and metastasis in cutaneous melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional tumor chemotherapy, which is most commonly applied as first-line therapy for cancer in the clinic, remains a formidable challenge due to the severe side effects and drug resistance (Alkhatib et al, 2022;Zhu et al, 2022a;Wang et al, 2022d;Kang et al, 2022). Through tremendous research by scientists, multifunctional nanozymes are proven to be a promising avenue to achieve higher tumor elimination efficacy in synergistic chemotherapy and catalytic therapy.…”
Section: Nanozymes In Chemotherapymentioning
confidence: 99%